Generalized converter modulation and loss estimation for grid interface applications - Gupta, R.; Ghosh, Arindam; Joshi, A. (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
In this paper, a generalized converter based on the cascaded H-bridge converter topology has been proposed to be used for the grid interface applications. This includes application of grid compensation and distributed generation interface to the grid. Basic H-bridge modules can be used to build a suitable three-phase voltage source converter (VSC) topology for any medium voltage distribution system application. A generalized multicarrier closed loop converter modulation has been used for the VSCs. The generalized converter modulation has a feature of equal loss distribution among each cell and all the device units in one cell are stressed uniformly. A methodology has been suggested to estimate the total losses in the converter circuit. This includes transformer losses, converter losses and passive component losses. The loss estimation is carried out for a single cell only and the total estimation is obtained by multiplication with the number of cascaded units. A case study of the application of shunt compensator for grid application has been considered to verify the proposed methodology modulation and loss estimation. The results are validated through PSCAD/EMTDC simulation studies.